2014
DOI: 10.1007/s00239-014-9632-1
|View full text |Cite
|
Sign up to set email alerts
|

Negative Purifying Selection Drives Prion and Doppel Protein Evolution

Abstract: The prion protein (PrP) when misfolded into the pathogenic conformer PrP Sc is the major causative agent of several lethal transmissible spongiform encephalopathies in mammals. Studies of evolutionary pressure on the corresponding gene using different datasets have yielded conflicting results. In addition, putative PrP or PrP interacting partners with strong similarity to PrP such as the doppel protein have not been examined to determine if the same evolutionary mechanisms apply to prion paralogs or if there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, it is to be expected that individuals with phenotypes corresponding to traits related to better production are being selected. Purifying selection has been reported for this same gene and its paralogous genes in some studies: the first was a sequence analysis in 26 mammalian species (37); the second was an evaluation of the PRNP gene in bovines and the results indicate that a strong purifying selection acted on this gene (38) and the third consisted in the exploration of the PRND gene that is paralogous to the PRNP gene and whose evolution has been by virtue of purifying selection among mammalian taxa (39). Sezgin et al reported that a complex selection favoring excessive replacement changes together with weak purifying selection possibly driven by frequency-dependent selection is driving PRNP sequence evolution (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is to be expected that individuals with phenotypes corresponding to traits related to better production are being selected. Purifying selection has been reported for this same gene and its paralogous genes in some studies: the first was a sequence analysis in 26 mammalian species (37); the second was an evaluation of the PRNP gene in bovines and the results indicate that a strong purifying selection acted on this gene (38) and the third consisted in the exploration of the PRND gene that is paralogous to the PRNP gene and whose evolution has been by virtue of purifying selection among mammalian taxa (39). Sezgin et al reported that a complex selection favoring excessive replacement changes together with weak purifying selection possibly driven by frequency-dependent selection is driving PRNP sequence evolution (40).…”
Section: Discussionmentioning
confidence: 99%
“…ZMYND11 encodes a transcriptional regulator protein that binds to adenovirus E1A proteins [ 12 ] while PRND encodes the doppel protein (Dpl), an evolutionarily related paralogue of PRNP believed to be involved in sperm maturation and capacitation [ 13 ]. Given the physical proximity between PRNP and PRND [ 14 ], as well as phylogenetic evidence that the two genes have been evolutionarily co-selected [ 15 ], we tested the hypothesis that strong selection within bovine PRND may be explanatory for selective signals previously detected in bovine PRNP [ 9 ]. Collectively, our analyses provide statistical support for intense purifying selection operating on bovine PRNP , with bovine PRND variation exhibiting no evidence for deviation from a strictly neutral model.…”
Section: Introductionmentioning
confidence: 99%